The effects of the European e-cigarette health warnings and comparative health messages on non-smokers' and smokers' risk perceptions and behavioural intentions - Catherine Kimber; Daniel Frings; Sharon Cox; Ian Albery; Lynne Dawkins (BMC, 2018)
Abstract Background Article 20 of the EU Tobacco Products Directive [TPD] stipulates that e-cigarette packets and refill products must carry a nicotine addiction health warning. Although previous studies conducted in North America have found that perceived harm, addictiveness and intention to use declined following exposure to e-cigarette health warnings, possible effects of the TPD health warnings on smokers and non-smokers has not been studied. This study will investigate the effects of the EU TPD e-cigarette health warnings and a comparative harm message (COMP; developed specifically for this study) on smokers' and non-smokers' perceptions of harm, addictiveness and social acceptability of e-cigarettes. Additionally, the potential effects of the TPD warnings and the COMP on smokers' intentions to purchase and use e-cigarettes will be explored. Methods/design A sample of 2400 UK residents will be recruited in this experimental, randomised design, with Smoking status (Smoker vs. Non-smoker), TPD presence (TPD1 vs. TPD2 vs. No-TPD) and COMP presence (Presence vs. Absence) as between subjects independent variables, and Time (pre-post exposure of images) as a within subjects factor. Dependent variables comprise self-reported perceived harm, addictiveness, social acceptability, e-cigarettes' effectiveness, intentions to purchase and use e-cigarettes. Cigarette dependence, previous e-cigarette exposure, and baseline intentions to quit will be measured as covariates. Discussion Health warnings, such as those implemented by the TPD, may help to prevent non-smokers from e-cigarettes use, but it is possible that they may inadvertently deter smokers from initiating use and substituting their tobacco smoking for e-cigarettes use if their content is deemed too negative. It is hoped that this study will help identify the most effective message or combination of messages that encourage use among smokers without promoting use among non-smokers. Trial registration ISRCTN registry ISRCTN76967031; date of registration: 23/10/18.